Effects of Prenatal Cannabinoids Exposure Upon Placenta and Development of Respiratory Neural Circuits - Eugenin-Leon, J; Bravo-Flores, K; Ochoa-Sarmiento, M; Caceres-Vergara, D (Springer, 2023)
Cannabis use has risen dangerously during pregnancy in the face of incipient therapeutic use and a growing perception of safety. The main psychoactive compound of the Cannabis sativa plant is the phytocannabinoid delta-9-tetrahydrocannabinol (A-9 THC), and its status as a teratogen is controversial. THC and its endogenous analogues, anandamide (AEA) and 2-AG, exert their actions through specific receptors (eCBr) that activate intracellular signaling pathways. CB1r and CB2r, also called classic cannabinoid receptors, together with their endogenous ligands and the enzymes that synthesize and degrade them, constitute the endocannabinoid system. This system is distributed ubiquitously in various central and peripheral tissues. Although the endocannabinoid system’s most studied role is controlling the release of neurotransmitters in the central nervous system, the study of long-term exposure to cannabinoids on fetal development is not well known and is vital for understanding environmental or pathological embryo-fetal or postnatal conditions. Prenatal exposure to cannabinoids in animal models has induced changes in placental and embryo-fetal organs. Particularly, cannabinoids could influence both neural and nonneural tissues and induce embryo-fetal pathological conditions in critical processes such as neural respiratory control. This review aims at the acute and chronic effects of prenatal exposure to cannabinoids on placental function and the embryo-fetal neurodevelopment of the respiratory pattern. The information provided here will serve as a theoretical framework to critically evaluate the teratogen effects of the consumption of cannabis during pregnancy. © 2023, Springer Nature Switzerland AG.